Computer engineering and technology : 20th CCF Conference, NCCET 2016, Xi'an, China, August 10-12, 2016, Revised selected papers /: 20th CCF Conference, NCCET 2016, Xi'an, China, August 10-12, 2016, Revised selected papers. (2016) - Unknown
No abstract available